Ghost forests of Marco Island: Mangrove mortality driven by belowground soil structural shifts during tidal hydrologic alteration. (15th November 2018) - Krauss, K.W.; Demopoulos, A.W.J.; Cormier, N.; From, A.S.; McClain-Counts, J.P.; Lewis, R.R.
Abstract: Land use changes often create in situ stress and eventual mortality in mangroves as unsuitable hydroperiods are created through tidal flow alterations. Here, we document mangrove forest and soil structural changes within transects established in tidally restricted areas on Marco Island (Collier County, Florida, USA), which has broad swaths of dead-standing or unhealthy mangroves ("ghost forests"). Transects (N = 4) were arranged to include full canopy, transitional, and open canopy (dead) forests, and compared to nearby reference forests. Aboveground and belowground carbon (C) stocks (Total C) ranged from 288 to 304 Mg C ha −1 on full canopy, transitional, and reference sites, which did not differ from each other. However, Total C was lower for dead sites (233 Mg C ha −1 ) dictated entirely by differences in aboveground C (live and dead trees, downed wood); no differences were found among forest condition in belowground C stocks. This belowground C has been persistent in the soil for 85 years since initial tidal restriction. Nevertheless, hydrologic rehabilitation has the potential to increase total C stocks on dead sites by 70–110 Mg C ha −1 . Collapse of the soil surface by 6–8 cm just under the active root zone in chronically stressed mangroves was evident within the bulk density profiles from transitional versus dead sites, suggesting that surface elevation loss as root turnover ceases may work correlatively with chronic stressors (anoxia, P limitation) to affect rapid mortality of forests over short periods of time many years after stress initiation. Hydrologic rehabilitation of stressed or denuded mangroves must also include an understanding of how these soil processes might be re-established. Graphical abstract: Image 1 Highlights: Soil collapse is a long-term consequence of altered tidal flushing in mangroves. Reduced root turnover vs. sustained decomposition facilitates root zone compaction. Compaction leads to elevation loss, greater flooding and anoxia, and mangrove death. With death, aboveground carbon was lost but soil carbon was largely preserved. Plans to restore hydrology should ameliorate soil surface elevation loss.